2022
DOI: 10.1101/2022.09.14.507939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Transcriptomic Network Responses to Divergent Acute Exercise Challenges in Young Adults

Abstract: Acute exercise elicits dynamic transcriptional changes that, when repeated, form the fundamental basis of adaptations in health, resilience, and performance. While moderate-intensity endurance training combined with conventional resistance training (traditional, TRAD) is often prescribed and recommended by public health guidance, high-intensity training combining maximal-effort intervals with intensive, limited-rest resistance training is a time-efficient alternative that may be used tactically (HITT) to seek … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Two to four hours after RE is typically considered the ideal time to detect changes in gene expression in skeletal muscle 8,9,70,104,105 . By contrast, our data show that the largest number of DEGs is detected 8 hours into recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Two to four hours after RE is typically considered the ideal time to detect changes in gene expression in skeletal muscle 8,9,70,104,105 . By contrast, our data show that the largest number of DEGs is detected 8 hours into recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Through reanalysis of the database obtained from GSE209880, 35 we found that both miR-92b-3p and miR-92b-5p expression in the skeletal muscle were increased after 24 h of a single exercise bout, as compared with baseline (Figure S7E). Consistently, we found that a single exercise bout upregulated the expression of both miR-92b-3p and miR-92b-5p in the skeletal muscle of mice (Figure S7D).…”
Section: Discussionmentioning
confidence: 99%